(untitled) (Acta Scientiarum. Biological Sciences, 2016)
Staphylococcus aureus infection may lead to the development of soft tissue damage. It has been evaluated in other researches using different animal models. In addition, the inflammatory response developed by the host organism facing an infection by this pathogen has been analyzed and neutrophils have been linked to the immune response developed. In this study, we aimed to compare the inflammatory response developed by the host induced by an intradermal infection with a methicillin-resistant strain of Staphylococcus aureus (MRSA) or a methicillin-susceptible strain of Staphylococcus aureus (MSSA). Mice euthanasia occurred in the following times: 6, 24, 48 and 96 hours of infection; the cell number and the cytokine release were evaluated. Our results showed that infections by different strains of Staphylococcus aureus lead to different immune response degrees. Although MRSA infection induces higher neutrophil recruitment to the infection site and higher inflammatory response in the draining lymph node, the increased production of TNF-Î±, IFN-Î³, IL-6 and IL-1Î² in the lymph node 6 hours after the infection was observed only in MSSA infected animals. Considering the data, MSSA may have mechanisms to prevent neutrophil recruitment to the infection site.